Biophysical Phenotyping and Modulation of ALDH+ Inflammatory Breast Cancer Stem‐Like Cells. Issue 5 (11th January 2019) - Chen, Weiqiang; Allen, Steven G.; Qian, Weiyi; Peng, Zifeng; Han, Shuo; Li, Xiang; Sun, Yubing; Fournier, Chelsea; Bao, Liwei; Lam, Raymond H. W.; Merajver, Sofia D.; Fu, Jianping
Abstract: Cancer stem‐like cells (CSCs) have been shown to initiate tumorigenesis and cancer metastasis in many cancer types. Although identification of CSCs through specific marker expression helps define the CSC compartment, it does not directly provide information on how or why this cancer cell subpopulation is more metastatic or tumorigenic. In this study, the functional and biophysical characteristics of aggressive and lethal inflammatory breast cancer (IBC) CSCs at the single‐cell level are comprehensively profiled using multiple microengineered tools. Distinct functional (cell migration, growth, adhesion, invasion and self‐renewal) and biophysical (cell deformability, adhesion strength and contractility) properties of ALDH+ SUM149 IBC CSCs are found as compared to their ALDH− non‐CSC counterpart, providing biophysical insights into why CSCs has an enhanced propensity to metastasize. It is further shown that the cellular biophysical phenotype can predict and determine IBC cells' tumorigenic ability. SUM149 and SUM159 IBC cells selected and modulated through biophysical attributes—adhesion and stiffness—show characteristics of CSCs in vitro and enhance tumorigenicity in in vivo murine models of primary tumor growth. Overall, the multiparametric cellular biophysical phenotyping and modulation of IBC CSCs yields a new understanding of IBC's metastatic properties and how they might develop and be targeted for therapeutic interventions. Abstract : This study comprehensively profiles the biophysical characteristics of inflammatory breast cancer stem‐like cells to delineate the so‐called "biophysical phenotype" of the model of the most metastatic breast cancer subtype. Evidence indicates that the cellular biophysical phenotype can predict and determine cancer cells' tumorigenic ability.